Sunken Worlds: The Past and Future of Human-Made Reefs in Marine Conservation. (7th August 2019) - Tickell, Sofia Castelló y; Sáenz-Arroyo, Andrea; Milner-Gulland, E J
Abstract: Structures submerged in the sea by humans over millennia provide hard and longstanding evidence of anthropogenic influence in the marine environment. Many of these human-made reefs (HMRs) may provide opportunities for conservation despite having been created for different purposes such as fishing or tourism. In the middle of controversy around the costs and benefits of HMRs, a broad analysis of biodiversity and social values is necessary to assess conservation potential. This requires reframing HMRs as social–ecological systems, moving beyond comparisons with natural coral or rocky reefs to consider their roles as ecosystems in their own right; creating frameworks to track their type, number, size, units, location, characteristics, origins, social uses, and associated biodiversity locally and worldwide; and applying systematic assessment of conservation benefits in relation to stated conservation intentions. This integrative approach can catalyze learning, identify conservation opportunities, and inform positive management of HMRs into the future.